Modelling the Impact of the Oil Sector on the Economy of Sultanate of Oman - Nasser Al-Mawali (International Journal of Energy Economics and Policy, 2016)
This study constructs and analyses a simple macroeconomic model that specifically tailored to model the impact of oil sector on the economy of Sultanate of Oman. The constructed model of the study measures the impact of oil sector on the Oman economy for the last three decades and also provides some forecasting for the major macroeconomics indicators related to the Oman economy. Model simulations indicate that the oil sector has large and positive impact on Oman GDP and its influence spills over to all other non-oil sectors of Oman economy. The study found that largest influence of oil was on the gas sector and the least economic sector influenced by oil was agricultural sector. The findings of the study suggest that Oman economy is far from being diversified and that the proposed model helps the policy makers in Oman to identify and forecast the impact of oil on other components of the Oman economy.